Wireless network security: 3G, 4G, wireless PAN/LAN/MAN - Pathan, Al-Sakib Khan (2012)
The presentation is about various facets of Wireless Network Security especially focusing on 3G, 4G, and Wireless PAN/LAN/MAN security aspects. The author's own views and contributions to the research community are also discussed.